Expensive Brains: “Brainy” Rodents have Higher Metabolic Rate - Sobrero, Raúl; May-Collado, Laura J.; Agnarsson, Ingi; Hernández, Cristián E. (Frontiers in Evolutionary Neuroscience, 2011)
Brains are the centers of the nervous system of animals, controlling the organ systems of the body and coordinating responses to changes in the ecological and social environment. The evolution traits that correlate with cognitive ability, such as relative brain size is thus of broad interest. Brain mass relative to body mass varies among mammals, and diverse factors have been proposed to explain this variation. A recent study provided evidence that energetics play an important role in brain evolution (Isler and van Schaik, 2006). Using composite phylogenies and data drawn from multiple sources, these authors showed that basal metabolic rate (BMR) correlates with brain mass across mammals. However, no such relationship was found within rodents. Here we re-examined the relationship between BMR and brain mass within Rodentia using a novel species-level phylogeny. Our results are sensitive to parameter evaluation; in particular how species mass is estimated. We detect no pattern when applying an approach used by previous studies, where each species body mass is represented by two different numbers, one being the individual that happened to be used for BMR estimates of that species. However, this approach may compromise the analysis. When using a single value of body mass for each species, whether representing a single individual, or available species mean, our findings provide evidence that brain mass (independent of body mass) and BMR are correlated. These findings are thus consistent with the hypothesis that large brains evolve when the payoff for increased brain mass is greater than the energetic cost they incur.